(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2019)
Repeated chromatographic separation and purification of the dichloromethane-methanol (1:1) extract of the stem bark of Calophyllum inophyllum led to the isolation of four secondary metabolites which were identified as β-friedelin (1), α-friedelan-3-ol (2), 4-hydroxyxanthone (3) and stigmast-5-en-3-one (4) by analysis of their NMR data and comparison with published values Dhaka Univ. J. Pharm. Sci. 18(2): 179-182, 2019 (December)